2004
DOI: 10.1176/appi.ajp.161.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cingulate, Gyrus Rectus, and Orbitofrontal Abnormalities in Elderly Depressed Patients: An MRI-Based Parcellation of the Prefrontal Cortex

Abstract: The prominent bilateral gray matter deficits in the anterior cingulate and the gyrus rectus as well as the orbitofrontal cortex may reflect disease-specific modifications of elderly depression. The differential pattern of abnormalities detected in the white matter and CSF compartments imply that distinct etiopathological mechanisms might underlie the structural cortical changes in these regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
236
4
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 351 publications
(259 citation statements)
references
References 62 publications
16
236
4
3
Order By: Relevance
“…Despite positive findings in other limbic regions in patients with MDD (eg, hippocampus; (Sheline et al, 1999)), the relation between treatment with antidepressants and ACC volume has not been systematically examined. While it is notable that in several studies reporting small ACC volumes, patients with MDD were free of medication for periods ranging between 2 and 4 weeks (Drevets et al, 1997;Lavretsky et al, 2007;Caetano et al, 2006;Ballmaier et al, 2004); it is unknown whether the withdrawal of antidepressants influenced the pattern of findings reported. Medication history is an important factor in studies of patients with MDD (Dickstein et al, 2005;Strasser et al, 2005;Frazier et al, 2005;Rajkowska, 2002) and our data further support the notion that even relatively short-term treatment may exert a measurable effect on the volumes of key brain regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite positive findings in other limbic regions in patients with MDD (eg, hippocampus; (Sheline et al, 1999)), the relation between treatment with antidepressants and ACC volume has not been systematically examined. While it is notable that in several studies reporting small ACC volumes, patients with MDD were free of medication for periods ranging between 2 and 4 weeks (Drevets et al, 1997;Lavretsky et al, 2007;Caetano et al, 2006;Ballmaier et al, 2004); it is unknown whether the withdrawal of antidepressants influenced the pattern of findings reported. Medication history is an important factor in studies of patients with MDD (Dickstein et al, 2005;Strasser et al, 2005;Frazier et al, 2005;Rajkowska, 2002) and our data further support the notion that even relatively short-term treatment may exert a measurable effect on the volumes of key brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Bremner et al (2002) and Pizzagalli et al (2004), who found no differences in BA25 or in BA32 (Bremner et al, 2002) volume between MDD patients and healthy controls, Coryell et al (2005) subsequently reported a reduction in left subcallosal gyrus volume in patients with MDD relative to controls. Finally, a number of studies demonstrate smaller gray (Lavretsky et al, 2007;Caetano et al, 2006;Ballmaier et al, 2004) and white (Ballmaier et al, 2004) matter volume in 'total' and in ventral (Tang et al, 2007) ACC in patients with MDD relative to controls; however, the cingulate regions assayed in these studies varied widely. A small number of studies have relied upon voxel-based morphometry (Pizzagalli et al, 2004;Chen et al, 2007;Tang et al, 2007) as opposed to manual delineation, as is common across the majority of studies.…”
Section: Introductionmentioning
confidence: 99%
“…These findings formed the basis of speculation that abnormalities in the subcorticalfrontal pathways may underlie the depression in some instances. Our findings indicate that smaller frontal lobe volumes in patients with MDD are circumscribed and occur in the anterior cingulate, gyrus rectus and the orbitofrontal regions (Ballmaier et al, 2004). Recently, our group (Ballmaier et al, 2007) demonstrated smaller hippocampal volumes, largely restricted to the CA1 and subiculum subfields in patients with late-life depression when compared with controls.…”
Section: Atrophymentioning
confidence: 49%
“…Volumetric reductions occur in patients diagnosed with late-life depression predominantly in the prefrontal regions and hippocampus when compared with controls (Steffens et al, 2002;Ballmaier et al, 2004). A reduction in the volume of the orbitofrontal cortex has been reported in patients with late-life depression (Lai et al, 2000).…”
Section: Atrophymentioning
confidence: 97%
“…Following the pioneering work by Bookstein, Grenander and Bajscy [4], [8], [22], the past several years have seen an explosion in the use of template matching methods in computer vision and medical imaging [3], [14], [24], [25], [30], [33], [36]- [40], [51], [53]- [56]. These methods have enabled the systematic measurement and comparison of anatomical shapes and structures in biomedical imagery leading to better understanding of neurodevelopmental, neuropsychiatric and neurological disorders in recent years [5], [6], [11], [13], [17], [20], [42]- [48], [50], [52], [59]. The mathematical theory of Grenander's deformable template models, when applied to these problems, involves smooth invertible maps (diffeomorphisms), as presented in this context in [55], [56], [14], [41], [36] and [33].…”
Section: Introductionmentioning
confidence: 99%